ANALISIS KOHESI DAN KOHORENSI DALAM WACANA BERITA KEMISKINAN DAN RAMADHAN DALAM KORAN REPUBLIKA - Permata Raharjo, Resdianto; Sudali, Ahmad (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This journal explains the results of cohesion and coherence analysis in the current new news discourse in Indonesia published by Republika, Thursday 16 May 2019. The research uses descriptive methods by describing and explaining the results of the analysis found in the study. This research is a type of qualitative research because the results tend to be released and descriptive. the technique used in this study is to take data, data collection is done in two ways, namely listening and taking notes. This study found the results of the use of cohesion and and the use of coherence. Cohesion is the integration between the parts that are characterized by the use of language elements. Cohesion is divided into two parts, lexical cohesion and grammatical cohesion. Grammatical cohesion includes conjunction, reference, release, substitution. Lexical cohesion includes antonyms, synonyms, repetitions, metonymy, and hypomini. Whereas, cohorence is the relationship between elements one with the other elements so that it has an integrated meaning.